1982
DOI: 10.1111/1523-1747.ep12497875
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Human Epidermal Cells Do Not Synthesize HLA-DR

Abstract: All nucleated cells express HLA-A, B, and C antigens. However, only a few cells, including epidermal cells, demonstrate HLA-DR antigens which are potent transplantation immunogens in man. The current study was undertaken to determine if epidermal cell continue to synthesize and/or express HLA-DR antigens after prolonged in vitro culture. Epidermal cells cultured for 7 days or more no longer stimulated allogeneic lymphocytes in the epidermal cell-lymphocyte reaction. Indirect immunofluorescence light microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…In 1983, the use of keratinocyte allografts was proposed as a potential solution to this problem (Hefton et al, 1983). This concept was based on the fact that cultured keratinocyte grafts in humans do not express major histocompatibility class II HLA-DR antigens (Morhenn et al, 1982). Further, the predominant source of class II antigens in skin, the Langerhans cells, do not persist in cultured keratinocyte grafts (Thivolet et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, the use of keratinocyte allografts was proposed as a potential solution to this problem (Hefton et al, 1983). This concept was based on the fact that cultured keratinocyte grafts in humans do not express major histocompatibility class II HLA-DR antigens (Morhenn et al, 1982). Further, the predominant source of class II antigens in skin, the Langerhans cells, do not persist in cultured keratinocyte grafts (Thivolet et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Except for minor differences, this multilayered epithelium matches its natural analogue [5] in its ultrastructural and bio chemical properties. Yet, it does not show cornification, nor does it contain Langer hans' cells [6], which are lost during cul ture. Subsequent to grafting, the cultured epithelium adheres firmly to the wound bed within 2 weeks and acquires all characteris tics of natural epidermis including the for mation of a stratum corneum.…”
Section: Josef a Ubock Peter Fritschmentioning
confidence: 97%
“…20,26,29,32 Human keratinocytes express major histocompatibility complex (MHC) class I antigens, but lack constitutive expression of MHC class II antigens 33,34 and therefore are considered ''non-professional'' antigen-presenting cells. [35][36][37] Because these types of skin substitutes do not contain professional antigen-presenting cells, such as Langerhans cells, acute rejection is not anticipated, and replacement by patient keratinocytes over time is expected. 38 Extensive clinical experience with Apligraf and other allogeneic treatments containing both epithelial cells as well as dermal fibroblasts show a lack of acute immune responses; however, it has also been shown that the cellular components of these treatments are lost within 6 to 8 weeks of placement.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
“…37 Preclinical studies demonstrated that NIKS-based BSS is negative for MHC class II human leukocyte antigen DR (HLA-DR) staining. 9 Moreover, expression of the co-stimulatory molecules B7-1, B7-2, and CD40 was not detectable.…”
Section: Skin Substitutes Generated From Niks Cells Do Not Express Kementioning
confidence: 99%